Menthol facilitates the intravenous self-administration of nicotine in rats - Wang, Tengfei; Wang, Bin; Chen, Hao (Frontiers in Behavioral Neuroscience, 2014)
Menthol is preferred by approximately 25% of smokers and is the most common flavoring additive in tobacco and electronic cigarettes. Although some clinical studies have suggested that menthol facilitates the initiation of smoking and enhances the dependence on nicotine, many controversies remain. Using licking as the operant behavior, we found that adolescent rats self-administering nicotine (30 μg/kg/infusion, free base, i.v.) with contingent oral menthol (60 μl, 0.01% w/v) obtained significantly more infusions than rats receiving a vehicle cue or rats self-administering i.v. saline with a menthol cue. Rats yoked to their menthol-nicotine masters emitted significantly fewer licks on the active spouts, indicating that contingent pairing between nicotine and menthol is required for sustained nicotine intake. Rats that self-administered nicotine with a menthol cue also exhibited a long-lasting extinction burst and robust reinstatement behavior, neither of which were observed in rats that self-administered saline with a menthol cue. The cooling sensation of menthol is induced by activating the transient receptor potential M8 (TRPM8) channel. When WS-23, an odorless agonist of the TRPM8 channel, was used as a contingent cue for nicotine, the rats obtained a similar number of nicotine infusions as the rats that were provided a menthol cue and exhibited a strong preference for the active spout. In contrast, highly appetitive taste and odor cues failed to support nicotine self-administration. These data indicated that menthol, likely by inducing a cooling sensation, becomes a potent conditioned reinforcer when it is contingently delivered with nicotine. Together, these results provide a key behavioral mechanism by which menthol promotes the use of tobacco products or electronic cigarettes.